Course-Integrated Learning Outcomes for Library Database Searching: Three Assessment Points on the Path of Evidence - Cmor, Dianne; Chan, Alison; Kong, Teresa (Evidence Based Library and Information Practice, 2010)
Objective - This study aims to assess student learning with respect to basic database searching at three different points within a required first year course. Methods - Three methods were employed at three different points to identify evidence of successful learning: 1. Analysis of in-class exercises from the initial library workshop, e.g. how many students showed evidence of satisfactorily achieving the stated learning outcomes. 2. Participant observation of student presentations, noting themes, strengths and weaknesses of student research strategy; written observation reports from librarians were coded and quantified to identify major themes. 3. Interviews with course instructors responsible for grading the final submitted projects, focusing on both student achievement and instructor perceptions of the impact of library involvement. Results - Though performance on in-class exercises showed evidence of successful learning in over 70% of students, observational data indicated that very few students showed evidence of applying new knowledge and new search skills to their own topics two weeks later. Instructor interviews revealed a perception of similar difficulties in final project submissions, and instructors suggested that students did not appreciate the need for library resources. Conclusion - In this study, students showed evidence of learning in a simulated environment, but were unable or unwilling to demonstrate this learning in authentic situations. Multiple assessment methods reveal a lack of student ability to apply search skills.